'Scary' pericytes: the fibrotic scar in brain and spinal cord lesions. Issue 1 (January 2022) - Rentsch, Nora H.; Rust, Ruslan
Abstract : Scar tissue presents a barrier to regeneration in the central nervous system (CNS). Although the glial scar has been extensively studied, recent evidence suggests that non-glial components are also involved. In a recent paper, Dias, Kalkitsas, and colleagues uncovered a subset of pericytes as a contributor to fibrotic scarring that is conserved across diverse CNS lesions.